The impact of different recovery times between matches on physical and technical performance according to playing positions - Penedo-Jamardo, E.; Rey, E.; Padrón-Cabo, A.; Kalén, A. (International Journal of Performance Analysis in Sport, 2017)
This research explores the influence of playing with different recovery times between matches on physical activity and technical performance. The sample was composed by 4496 professional players who participated in German professional league (Deutsche Fußball Liga - DFL) during the season 2011-2012. Data were collected using a semi-automatic optical tracking system (VISTRACK, by Impire Corp., Germany). Differences on work rate profiles of soccer players were analysed for the following variables: total distance covered, number of fast runs, number of sprints and percentage of successful passes. The main finding of this study suggests that the total distance covered, the number of fast runs and the number of sprints decreased in professional soccer players in microcycles with length of <4 days during the mid-season. Central defenders, external defenders and external midfielders covered less total distance in microcycles of <4 days, and this effect was more evident during the mid-season. During three-day microcycles in comparison to four-day cycles, central defenders and external defenders reduced the total distance covered. No differences were observed between teams according to the team quality and match location. Coaches should pay extra attention to adapt recovery strategy according to playing position and period of season.